2006
DOI: 10.1002/j.2158-1592.2006.tb00227.x
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Logistics Management in a Post-Soviet Central Asian Transitional Economy

Abstract: The research presented explores the logistics management of European and North American manufacturing companies operating in the unique environment of the post‐Soviet Central Asian transitional economy of Kazakhstan. Combining three alternating phases of quantitative and qualitative analysis, the research identifies the challenges logistics managers face in their efforts to distribute their companies' products into and within Kazakhstan. Then, using cross‐case analysis on a series of eleven case studies of Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…To illustrate, the inclusion of the additional term "global" or "international" in the search resulted in less than one-third of our sample (2,266 records). Studies that would have been overlooked with this approach included Price's (2006) model for logistics management in a post-soviet central Asian transitional economy, van Bodegraven's (2001) overview of the state of logistics in Cuba, and Zhu and Sarkis's (2004) investigation on green supply chain management practices in Chinese manufacturing firms. This step of the process was conducted by an international graduate student majoring in Supply Chain Management at a university in the Midwestern U.S., and it resulted in a total of 809 articles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To illustrate, the inclusion of the additional term "global" or "international" in the search resulted in less than one-third of our sample (2,266 records). Studies that would have been overlooked with this approach included Price's (2006) model for logistics management in a post-soviet central Asian transitional economy, van Bodegraven's (2001) overview of the state of logistics in Cuba, and Zhu and Sarkis's (2004) investigation on green supply chain management practices in Chinese manufacturing firms. This step of the process was conducted by an international graduate student majoring in Supply Chain Management at a university in the Midwestern U.S., and it resulted in a total of 809 articles.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 17 manuscripts were published in the Journal of Business Logistics (JBL). Articles within this subset covered logistics practices in various countries, such as Cuba (Van Bodegraven 2001) and Kazakhstan (Price 2006), and the integration of logistics and marketing (Ellinger, Daugherty, and Keller 2000;Mollenkopf, Gibson, and Ozanne 2000). Noteworthy are the special issues on European L&SCM research (Gammelgaard 2006(Gammelgaard , 2008 and the international logistics section of the annotated bibliography covering L&SCM-related dissertations (Stock and Broadus 2006).…”
Section: Common Themes Investigated In the International Journal Of Omentioning
confidence: 99%
See 1 more Smart Citation
“…The availability and quality of infrastructure is one of the key components in determining the logistics environment of a country (Price, 2006). In general, it can be observed that in terms of both infrastructure and services, each individual mode of transport in Vietnam suffers from limited capacity and capability.…”
Section: Transport and Logistics Infrastructurementioning
confidence: 99%
“…In 1991, at a meeting in Almaty -the capital of Kazakhstan at the timeall five ex-Soviet countries of Central Asia joined the Community of Integrated States (CIS), which in 1993 came to include all of the formerly Soviet republics with the exception of the three Baltic states, namely Estonia, Latvia and Lithuania. O'Driscoll, Holmes and Kirkpatrick (2001) described Turkmenistan and Uzbekistan as "repressed" relative to Kazakhstan, the Kyrgyz Republic and Tajikistan. What has been published is largely focused on single country studies, for example, Azerbaijan (Rustamov, 2009), Kazakhstan (Dana, 1997;Price, 2006), the Kyrgyz Republic (Dana, 2000), and Turkmenistan (Miller, 2009). Comparative studies are few (e.g., KaDownloaded by [Selcuk Universitesi] at 15:11 20 December 2014 zakhstan and the Kyrgyz Republic: Luthans and Ibraveva, 2006).…”
Section: Introductionmentioning
confidence: 99%